Edukasi Dan Pelatihan Budidaya Tanaman Obat Keluarga (Toga) Di Desa Parasrejo, Kabupaten Pasuruan - Hidayanto, Fajar; Priyambodo, Danang; Ningrum, Lanny Puspita; Purnomo, Andzikriyanto; Abadi, Muhammad Imam; Mukhlason; Mu’minin, Mokh. Amirul; Laila, Yunita Nur (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Family medicinal plants (TOGA) are the choice to change people's habits back to traditional habits in curing various diseases. TOGA is very easy to find like some plants in Parasrejo Village, but not many people understand the types of family medicinal plants, how to cultivate them and their properties. The purpose of this service is to explain and practice several types of TOGA for planting in the yard. The service method starts with observing the surrounding environment, outreach to the community and village officials and then creating a TOGA garden. The plants grown in the garden include Asian lavender, pandanus, aloe vera, galangal, tomatoes, ginger, kencur and basil. The results of the service show that the people of Parasrejo Village already understand a number of species and are very enthusiastic about participating in socialization and trying to plant several family medicinal plants